2021
DOI: 10.1093/ehjci/jeab268
|View full text |Cite
|
Sign up to set email alerts
|

Progressive left and right heart dysfunction in coronavirus disease-19: Prospective echocardiographic evaluation

Abstract: Aims Cardiac dysfunction in coronavirus disease-19 (COVID-19) has been reported during acute phase but serial changes have not been well studied. To determine serial changes in type and severity of echocardiographic left and right heart functions we performed a prospective study. Methods and results Successive COVID-19 patients at discharge from the hospital from June to December 2020 were enrolled. Clinical details were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
0
10
0
2
Order By: Relevance
“…A prospective echocardiographic study of hospitalized, symptomatic patients with COVID-19 reported a decrease in both left and right-sided cardiac function 3 months after hospital discharge. 20 Preliminary findings of the prospective longitudinal study C-MORE (Capturing MultiORgan Effects of COVID-19) 21 showed that more than half of the patients experienced symptoms at 6 months after COVID-19, limiting their ability to exercise. C-MORE investigators also noted a dissociation between symptoms and objective measures of CV health.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective echocardiographic study of hospitalized, symptomatic patients with COVID-19 reported a decrease in both left and right-sided cardiac function 3 months after hospital discharge. 20 Preliminary findings of the prospective longitudinal study C-MORE (Capturing MultiORgan Effects of COVID-19) 21 showed that more than half of the patients experienced symptoms at 6 months after COVID-19, limiting their ability to exercise. C-MORE investigators also noted a dissociation between symptoms and objective measures of CV health.…”
Section: Discussionmentioning
confidence: 99%
“…More than 50% of the 50 patients who recovered from COVID-19 had reduced right ventricular ejection fraction [134]. Chaturvedi et al classified 1,000 patients with COVID-19 into mild, moderate, and severe according to preexisting cardiovascular disease and the degree of COVID-19 infection and found that moderate to severe cases showed extreme cardiac damage than mild COVID-19 cases, with progressive decline in cardiac function over 3 months (LVEF −1.1 ± 0.3 vs. −3.8 ± 0.3%; mitral E/e' +3.2 ± 0.1 vs. +4.8 ± 0.1; tricuspid Vmax + 0.3 ± 0.1 vs. +1.0 ± 0.1 cm; TAPSE −0.7 ± 0.2 vs. −2.7 ± 0.2 mm (P < 0.001)) [135]. Cardiac structure (left ventricular volume, mass, and atrial area), function (ejection fraction, global longitudinal shortening, and aortic dilation), tissue characteristics (T1, T2, extracellular volume fraction mapping, and late gadolinium enhancement), and biomarkers (troponin, Nterminal pro-B-type natriuretic peptide) in patients with mild symptoms (troponin-negative, asymptomatic, or mildly symptomatic) after recovery from COVID-19 were not significantly different from those in COVID-19 seronegative healthy controls [136].…”
Section: Covid-19 and Cardiovascular Diseasesmentioning
confidence: 86%
“…Several ailments have been described following COVID‐19 infection, 42 and although RV function has been reported to both improve and deteriorate after recovery of COVID‐19 infection, LV function does not seem to improve and may even deteriorate, particularly in moderate‐severe infection but also in mild cases. 43 , 44 Hence, the consequences of COVID‐19 go beyond the immediate infection, and the clinical implications of persistent LV dysfunction need to be explored further.…”
Section: Discussionmentioning
confidence: 99%